Nivel de conocimiento del paciente diabético tipo 2 sobre su enfermedad en el HGZ/MF No2 - Ramos Duarte, Alejandra Lizbeth (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
INTRODUCTION: Diabetes Mellitus type 2 (DM2) is a public health problem as it is the third cause of death in Mexico, complications are frequent due to chronic lack of control of the patient, so an adequate level of knowledge positively influences their glycemic control. to reduce morbidity and mortality. OBJECTIVE: To determine the level of knowledge of the patient with type 2 diabetes mellitus about his disease in the HGZ/MF No.2. MATERIAL AND METHODS: Cross-sectional, observational and prospective study. Carried out in the outpatient clinic of HGZ/MF No.2, from February to June 2022, to patients diagnosed with DM2, of both sexes, over 18 years of age, who agreed to participate in the study. The "Knowledge Test on Diabetes Mellitus" validated by Campos et al. with Cronbach's alpha 0.89. Descriptive and X2 statistics were performed to determine the association between categorical variables with p < 0.05. Registration Number: R-2021-1603-009. RESULTS: 356 patients with DM2 were evaluated, between 18 and 60 years of age, 62.3% female and 37.64% male, 48.02% with secondary level, 70.5% married. 88% obtained a low level of knowledge. Only 19.09% found good glycemic control. An association was found between the level of knowledge with the patient's complications: 87.1% had had some complication, predominantly renal in 18.82%, neuropathies 17.69% and circulatory 15.73%. CONCLUSIONS: The level of knowledge in patients with DM2 of HGZ/MF No.2 is low, justifying the large percentage of lack of control and complications in our population. A lower level of knowledge is more frequently associated with older age, lower education level, greater glycemic lack of control, and complications.

INTRODUCCIÓN: La Diabetes Mellitus tipo 2 (DM2) es un problema de salud pública al ocupar la tercera causa de muerte en México, las complicaciones son frecuentes debido al descontrol crónico del paciente por lo que un adecuado nivel de conocimiento influye positivamente en su control glicémico para disminuir la morbimortalidad. OBJETIVO: Determinar el nivel de conocimiento del paciente con diabetes mellitus tipo 2 sobre su enfermedad en el HGZ/MF No.2. MATERIAL Y MÉTODOS: Estudio transversal, observacional y prospectivo. Realizado en la consulta externa del HGZ/MF No.2, de febrero a junio 2022, a pacientes con diagnóstico de DM2, de ambos sexos, mayores de 18 años, que aceptaron participar en el estudio. Se utilizó la “Prueba de conocimientos sobre la Diabetes Mellitus” validada por Campos y Cols. con alfa de Cronbach 0.89. Se realizó estadística descriptiva y X2 para determinar asociación entre variables categóricas con p < 0.05. Número Registro: R-2021-1603-009. RESULTADOS: Se evaluaron 356 pacientes con DM2, entre 18 y 60 años de edad, del sexo femenino 62.3% y masculino 37.64%, con nivel secundaria 48.02%, casados 70.5%. El 88% obtuvo nivel bajo de conocimiento. Solo el 19.09% se encontró con buen control glicémico. Se encontró asociación entre nivel de conocimiento con las complicaciones de paciente el 87.1% habían tenido alguna complicación predominando las renales en 18.82%, neuropatías 17.69% y circulatorias 15.73%. CONCLUSIONES: El nivel de conocimiento en pacientes con DM2 del HGZ/MF No.2 es bajo, justificando el gran porcentaje de descontrol y complicaciones en nuestra población. Un menor nivel de conocimiento se asocia en mayor frecuentemente a una mayor edad, escolaridad baja, mayor descontrol glicémico y complicaciones.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18756; info:eu-repo/classification/cti/3; FCMB-E-2024-0193; Diabetes mellitus tipo 2; Nivel de conocimiento; Medicina familiar